PENERAPAN MODEL DISCOVERY LEARNING BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA1 PADA MATERI HIDROKARBON - Nurhalija, Wa Ode Siti; Ratna, Ratna; Marhadi, Muh. Alim (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2021)
Research has been carried out to improve student learning outcomes XI IPA1 SMA Negeri 1 Bone through a discovery learning model based on a scientific approach to hydrocarbon material. This study aims to, 1) determine the description of the learning outcomes of class XI IPA1 SMA Negeri 1 Bone on hydrocarbon material throgh the application of discovery learning based on a scientific approach, 2) to determine the effectiveneness of discovery learning model based on scientific approach to improving learning outcomes in class XI IPA1 SMA Negeri 1 Bone on hydrocarbon material, 3) knowing the implementation of learning hydrocarbon material with the application of discovery learning model based on the scientific approach in SMA Negeri 1 Bone, 4) knowing the students’ response to the application of discovery learning model based on the scientific approach to hydrocarbon materia. The data collection technique was done by giving pre-test and post-test with research instruments in the form of multiple choice questions totaling 20 items, student activity observation sheets, teacher activity observation sheets, and questionnaire sheets or student responses to the learning process. Student learning outcomes with discovery learning models obtained an average value of 79,13. There is an increase in student learning outcomes using discovery learning models based on a scientific approach. This can be seen through the N- Gain analysis, it can be stated that the discovery learning model with a scientific approach can improve student learning outcomes by obtaining an average value of 0,68.